A study to Assess the Student’s Anxiety Level about Examination During Lock Down in Selected Colleges of Pune City - Priyanka Kadam1 , Mangesh Jabade1 , Tejashri Ligade1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
While whole world is facing the outbreak of COVID-19, universities are crucially affected at their core: Thestudents. For them, the period is undoubtedly very stressful: classes are moved online, semesters abroad arepostponed, examinations and how they are conducted remain uncertain. As universities have gone virtualwithin a matter of days, how have these affected students? For the students the stress and anxiety level isvery high due to lock down. 1Due to COVID-19 student’s anxiety level about examination has become very serious issue now days.College students are experiencing very serve anxiety level due to the lock down. . When stress is perceivednegatively or becomes excessive, it leads to anxiety before and during examinations and ultimately affectstheir academic achievement. As due to the pandemic situation many classes were conducted online mode ofteaching but as theCOVID -19situation is not yet under control students anxiety level is increasing day by day about theirexamination2. The present study was conducted to know the examinations anxiety felt by college studentsdue to lock down. The sample consisted of 60 college students drawn using Non Probability conveniencesampling method from selected colleges of city studying in Professional Courses (Including first year,Second year, Third year and Fourth year respectively) . A questionnaire was developed by the researcherto access examination anxiety among college students. The result shows correlation between examinationand anxiety of college students due to lock down. Design - The present study is a descriptive research. Thedata was collected from the primary sources. Results- Non Probability convenience sampling techniqueused to collect information from 60 participants studying in colleges of Pune city. And found that out of 60participants who participated in the current study the results were 50% students have very severe anxietylevel, 20% have severe anxiety, 20% moderate level of anxiety and 5% have Mild anxiety and reaming5% no anxiety level about their upcoming examinations Conclusion- This study was mainly conducted toassess the students anxiety level about examination during lock down .and it is understood that students aresuffering with anxiety level. .